Sarcomatoid carcinomas of the gallbladder: clinicopathologic characteristics - (:unkn) unknown (SPRINGER, 2019)
Sarcomatoid carcinomas recently came into the spotlight through genetic profiling studies and also as a distinct model of epithelial-mesenchymal transition. The literature on sarcomatoid carcinomas of gallbladder is limited. In this study, 656 gallbladder carcinomas (GBC) were reviewed. Eleven (1.7%) with a sarcomatoid component were identified and analyzed in comparison with ordinary GBC (O-GBC). Patients included 9 females and 2 males (F/M = 4.5 vs. 3.9) with a mean age-at-diagnosis of 71 (vs. 64). The median tumor size was 4.6 cm (vs. 2.5; P = 0.01). Nine patients (84%) presented with advanced stage (pT3/4) tumor (vs. 48%). An adenocarcinoma component constituting 1-75% of the tumor was present in nine, and eight had surface dysplasia/CIS; either in situ or invasive carcinoma was present in all cases. An intracholecystic papillary-tubular neoplasm was identified in one. Seven showed pleomorphic-sarcomatoid pattern, and four showed subtle/bland elongated spindle cells. Three had an angiosarcomatoid pattern. Two had heterologous elements. One showed few osteoclast-like giant cells, only adjacent to osteoid. Immunohistochemically, vimentin, was positive in six of six; P53 expression was >60% in six of six, keratins in six of seven, and p63 in two of six. Actin, desmin, and S100 were negative. The median Ki67 index was 40%. In the follow-up, one died peri-operatively, eight died of disease within 3 to 8 months (vs. 26 months median survival for O-GBC), and two were alive at 9 and 15 months. The behavior overall was worse than ordinary adenocarcinomas in general but was not different when grade and stage were matched. In summary, sarcomatoid component is identified in < 2% of GBC. Unlike sarcomatoid carcinomas in the remainder of pancreatobiliary tract, these are seldom of the osteoclastic type and patients present with large/advanced stage tumors. Limited data suggests that these tumors are aggressive with rapid mortality unlike pancreatic osteoclastic ones which often have indolent behavior.
Keywords: Gallbladder; Carcinoma; Adenocarcinoma; Sarcoma; Sarcomatoid; OSTEOCLASTIC GIANT-CELLS; UNDIFFERENTIATED CARCINOMA; SMALL-INTESTINE; CARCINOSARCOMA; BREAST; DIAGNOSIS; PANCREAS; FEATURES